British drama of the industrial revolution - Burwick, Frederick 1936-2022 (Cambridge Univ. Press, 2015)
Between the advent of the French Revolution and the short-lived success of the Chartist Movement, overworked and underpaid labourers struggled to achieve solidarity and collective bargaining. That history has been told in numerous accounts of the age, but never before has it been told in terms of the theatre of the period. To understand the play lists of a theatre, it is crucial to examine the community which that theatre serves. In the labouring-class communities of London and the provinces, the performances were adapted to suit the local audiences, whether weavers, or miners, or field workers. Examining the conditions and characteristics of representative provincial theatres from the 1790s to 1830s, Frederick Burwick argues that the meaning of a play changes with every change in the performance location. As contributing factors in that change, Burwick attends to local political and cultural circumstances as well as to theatrical activities and developments elsewhere